(untitled) (Surkhet Journal, 2014)
The indirect written feedback is more effective than direct written feedback to improve the ESL writing skills. The ESL learners can be facilitated with the indirect written feedback which indicates the errors with underlining, circling, and marking the selected errors. The learners can produce better writing if they are being rendered constant critical pedagogical feedback. The indirect corrective written feedback should‌ be‌ feasible‌ to‌ help‌ the‌ learners‌ elevate‌ their‌ academic‌ writing‌ skills.‌ A‌ finding‌ of‌ the‌ study‌ was‌ that the teachers usually adopted oral and direct feedback to improve writing skills.